Separate worlds: a discourse analysis of mainstream and Aboriginal populist media accounts of the Northern Territory Emergency Response - Fiona Proudfoot; Daphne Habibis (2014)
Critical commentary about the Northern Territory Emergency Response (NTER) has included the claim that the media presented a simplistic and stereotyped image of Aboriginal communities at the time of its introduction in 2007, but to date there has been no systematic analysis to support this. This study addresses this research gap through a critical discourse analysis of reportage of the NTER in mainstream and Aboriginal populist print media. The findings reveal major differences in these accounts, with radically different propositions and normative assumptions. Mainstream media were overwhelmingly negative in their portrayal of remote Aboriginal communities, were silent about Aboriginal resistance and portrayed urgent Commonwealth intervention as necessary and heroic. The Aboriginal media provided contextualised accounts of the issues and focused intensely on the human rights implications of the intervention. The findings reveal a concerning racialised divide in representations of the issues facing remote Aboriginal communities in 2007 that helps to explain why the Australian public accepted policies that discriminated against Australia’s First Nations peoples.